User-generated branding via social media: An examination of six running brands. Issue 3 (June 2017) - Geurin, Andrea N.; Burch, Lauren M.
Highlights: User-generated content elicited greater engagement than brand-generated content. Photos with an overt brand focus were most successful in eliciting engagement. Differentiation strategy brands received more engagement than best-cost providers. Abstract: The increased global popularity of social media has led many consumer brands to increasingly turn to consumer-to-consumer marketing methods in recent years. One such method, user-generated branding (UGB), is defined as "the strategic and operative management of brand related user-generated content (UGC) to achieve brand goals" (Burmann & Arnhold, 2009, p. 66). Other disciplines have identified potential benefits of UGB such as cost effectiveness, the ability to track consumers, and immediate feedback regarding a brand and its products or services (Burmann, 2010). Hambrick and Kang (2015) also posited that UGB might be effective in developing stronger relationships between brands and consumers and eliciting greater engagement with consumers on social media. This study sought to fill the gap on UGB research within the sport management field. Utilising Porter's (1985) generic strategies as a theoretical framework, the Instagram accounts of six purposefully selected running brands were examined to determine to what extent brands utilised user-generated content on their Instagram accounts and whether differences existed in audience engagement based on the type of content posted. A quantitative content analysis method was employed, and results indicated that those brands utilising a differentiation strategy and posts with an overt focus on the product or brand were most successful in eliciting engagement from followers. Implications for researchers and practitioners are discussed in greater detail in the paper.